Addressing Adolescent Smoking Cessation through Innovative Approaches: A Call for Action - Radian Ilmaskal; Rinaldi Daswito (RRZ Scientific Publishing, 2024)
The issue of adolescent smoking represents a significant challenge to global public health, contributing markedly to the burden of disease and mortality on a global scale. Despite the implementation of numerous strategies to reduce tobacco consumption, the prevalence of smoking among adolescents remains a significant concern, particularly in low- and middle-income countries (LMICs). The use of tobacco during adolescence not only increases the risk of developing chronic diseases such as cardiovascular disease and cancer but also presents challenges to smoking cessation due to the addictive properties of nicotine and the sociocultural factors influencing youth behavior. This paper is expected to offer valuable insights into the potential of technology-based solutions to support smoking cessation among adolescents, contributing to broader efforts to reduce tobacco-related morbidity and mortality on a global scale.